Pengembangan Model Permainan â€œVoltacerâ€ Bola Voli Kelas VII SMP Negeri 1 Godong (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the Game Model Development "Voltacer" extra-curricularvolleyball in grade 1 SMP Negeri 1 Godong District of Godong Grobogan. This study uses pengembanganyangresearch refers to the model development (research-based devolepment) of Sugiyono. The results of the study of small-scale test results obtained from the evaluation of the percentage is 84.28% penjas experts (meet bothcriteria), whereas the percentage of expert learning I was 90.00% (meets both criteria), expert pembeajaran IIwas 88.87% (meet both criteria). The results of the questionnaire the percentage of students in a small-scale test was 91.48% (meets criteria very well. Meanwhile, from the student questionnaire in a large-scale test results obtained percentage of 95.70% (meets criteria very well).Based on the research results, it can be concluded that the model of the game "voltacer" volley ball can be used for class VII student extracurricular khususya SMP Negeri 1 Godong. Suggestions submitted penjasorkes that teachers should use the model of the game "voltacer" volleyball volleyball in the delivery of material by adjusting the infrastructure and facilities available in the school